112k views
4 votes
I don't understand what the answer is supposed to be, none of my answers match.

I don't understand what the answer is supposed to be, none of my answers match.-example-1

1 Answer

2 votes

The rational expression is the following


((x-1)/(6xy))/((5)/(2y))

By applying the sandwich rule:

we have


((x-1)/(6xy))/((5)/(2y))=((x-1)(2y))/((6xy)(5))

which gives


((x-1)/(6xy))/((5)/(2y))=((x-1)(2y))/((6xy)(5))=((x-1)(2y))/((2\cdot3xy)(5))=((x-1)(2y))/((3x\cdot2y)(5))=(x-1)/(3x\cdot5)=(x-1)/(15x)

then, the answer is option 2.

I don't understand what the answer is supposed to be, none of my answers match.-example-1
User Rguerrettaz
by
5.2k points